Clothianidin decomposition in Missouri wetland soils. Issue 1 (18th January 2021) - Beringer, Chelsey J.; Goyne, Keith W.; Lerch, Robert N.; Webb, Elisabeth B.; Mengel, Doreen
Abstract: Neonicotinoid pesticides can persist in soils for extended time periods; however, they also have a high potential to contaminate ground and surface waters. Studies have reported negative effects associated with neonicotinoids and nontarget taxa, including aquatic invertebrates, pollinating insect species, and insectivorous birds. This study evaluated factors associated with clothianidin (CTN) degradation and sorption in Missouri wetland soils to assess the potential for wetland soils to mitigate potential environmental risks associated with neonicotinoids. Solid‐to‐solution partition coefficients ( K d ) for CTN sorption to eight wetland soils were determined via single‐point sorption experiments, and sorption isotherm experiments were conducted using the two most contrasting soils. Clothianidin degradation was determined under oxic and anoxic conditions over 60 d. Degradation data were fit to zero‐ and first‐order kinetic decay models to determine CTN half‐life ( t 0.5 ). Sorption results indicated CTN sorption to wetland soil was relatively weak (average K d, 3.58 L kg –1 ); thus, CTN has the potential to be mobile and bioavailable within wetland soils. However, incubation results showed anoxic conditions significantly increased CTN degradation rates in wetland soils (anoxic average t 0.5, 27.2 d; oxic average t 0.5, 149.1 d). A significant negative correlation was observed between anoxic half‐life values and soil organic C content ( r 2 = .782; p = .046). Greater CTN degradation rates in wetland soils under anoxic conditions suggest that managing wetlands to facilitate anoxic conditions could mitigate CTN presence in the environment and reduce exposure to nontarget organisms. Core Ideas: Clothianidin degradation is more rapid under anoxic conditions in Missouri wetland soils. SOC negatively correlated with CTN half‐life values under anoxic conditions. Clothianidin has a weak sorption affinity for the Missouri wetland soils studied. Anoxic conditions may be a viable strategy to mitigate Clothianidin presence in wetland soils.